1991
DOI: 10.1111/j.1445-5994.1991.tb01405.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double‐blind trial of cyclosporin and azathioprine in refractory rheumatoid arthritis

Abstract: Fifty-two patients with severe rheumatoid arthritis (RA) from four Australian centres were randomised to receive cyclosporin A (CSA) (n = 25) or azathioprine (AZA) (n = 27) for six months. Initial mean doses of CSA and AZA were 4.2 mg/kg and 1.7 mg/kg respectively. The mean doses of CSA and AZA at six months were 3.4 mg/kg and 1.9 mg/kg. Assessments of side-effects and outcomes of benefit were made monthly by independent, blinded observers. Both treatment groups exhibited statistically significant improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…Over the years, CyA has been proven to be more effective than placebo in disease control [5][6][7][8][9], even at long term [10], delaying radiological progression [11][12][13]. Controlled trials have shown CyA to be as effective as parenteral gold [14,15], D-penicillamine [16], hydroxychloroquine (HCQ) and azathioprine (AZA) [17][18][19], but less effective than methotrexate (MTX) [20][21][22].…”
Section: Cyclosporine a In Rheumatoid Arthritismentioning
confidence: 99%
“…Over the years, CyA has been proven to be more effective than placebo in disease control [5][6][7][8][9], even at long term [10], delaying radiological progression [11][12][13]. Controlled trials have shown CyA to be as effective as parenteral gold [14,15], D-penicillamine [16], hydroxychloroquine (HCQ) and azathioprine (AZA) [17][18][19], but less effective than methotrexate (MTX) [20][21][22].…”
Section: Cyclosporine a In Rheumatoid Arthritismentioning
confidence: 99%
“…Sampling from conditional distributions Azathioprine G Azathioprine HAQ: none of the trials in the Cochrane library (azathioprine versus placebo, three trials including a grand total of 33 patients treated with effective doses of azathioprine) gives HAQ data. 62 G Only one of the studies, of azathioprine against other DMARDs, [63][64][65][66][67] appears to have HAQ data, but the azathioprine group in this study only had 27 patients. 67 The patients appeared to be a group with severe disease (baseline HAQ scores of 1.8).…”
Section: Appendixmentioning
confidence: 89%
“…62 G Only one of the studies, of azathioprine against other DMARDs, [63][64][65][66][67] appears to have HAQ data, but the azathioprine group in this study only had 27 patients. 67 The patients appeared to be a group with severe disease (baseline HAQ scores of 1.8). Change in HAQ at 6 months was recorded at 0.1 for azathioprine and for ciclosporin groups.…”
Section: Appendixmentioning
confidence: 89%
“…More recently, CsA has been increasingly used to treat diverse autoimmune disorders refractory to corticosteroids or other immunosuppressive agents (6). Randomized placebo-controlled trials have shown CsA to be effective in autoimmune uveitis (6,192), Behcet's syndrome (193), psoriasis (194), inflammatory dermatoses (6,195), inflammatory bowel disease (196)(197)(198)(199), primary biliary cirrhosis (200), rheumatoid arthritis (6,201,202), aplastic anemia (6), myasthenia gravis (6), chronic inflammatory demyelinating polyneuropathies (6), and nephrotic syndrome (6,137).Concomitant corticosteroid therapy may enhance response (6,199). Improvement may occur promptly (often within 1 to 3 wk of initiation of CsA), but relapse has been frequent upon its discontinuation (6,195,203).…”
Section: Cyclosporin Amentioning
confidence: 99%